SPREAD OF COVID-19 IN MOROCCO DISCRETE MATHEMATICAL MODELING: OPTIMAL CONTROL STRATEGIES AND COST-EFFECTIVENESS ANALYSIS. (2020) - KADA, DRISS; LABZAI, ABDERRAHIM; BALATIF, OMAR; RACHIK, MOSTAFA; LABRIJI, EL HOUSSINE
No abstract available